Difabel dalam Alquran - Sri Handayana (INKLUSI, 2016)
This paper is a descriptive analysis of the Quranic views and attitudes on the people with disabilities. It starts with examining verses from the Quran and Prophetic Traditions (Hadith) as well as relevant social reality. Despite the fact that the Quran teaches equality and diversity, Muslims attitudes towards people with disabilities may vary, depending on their perspectives of disability influenced not only by their faith but also their social context. This paper even tries to give a particular emphasis on hidden social messages in the Quran that should be implemented in current everyday life.[Tulisan ini bertujuan mendeskripsikan pandangan serta sikap Alquran terhadap difabel. Penafsiran dimulai dari menelusuri ayat-ayat yang berhubungan dengan difabel dan selanjutnya dihubungkan dengan realitas sosial. Sekalipun Alquran mengajarkan kesetaraan dan keragaman, sikap umat Islam terhadap difabel mungkin saja berbeda tergantung perspektif mereka terhadap difabel dan lingkungan sosial di mana mereka berada. Tulisan ini juga mencoba untuk mengeksplorasi secara mendalam pesan-pesan sosial tersembunyi dari Alquran terkait difabel sehingga dapat diimplementasikan pada zaman sekarang.]